Research on Combined Numerical Integral Algorithms in Structure Seismic Hybrid Testing - Wang, Xiao Feng; Cai, Xin Jiang; Tian, Shi Zhu (Applied Mechanics and Materials, 2012)
ΛεεThe explicit integral algorithms is not requiring iteration but needing a conditional stable, and the implicit integral algorithms is unconditionally stable but requiring iteration. In this paper, a modified Wilson θ method that named CD-Wilson θ method is established, the center difference method is used as explicit integral algorithms and Wilson θ method is used as implicit integral algorithms. And the amplification matrix is used to explore the stability and the precision according to calculation and deduction. The results show that conclusions of stability condition is θΩE≤2 , the problem of constrained time step of CD-Newmark is solved, and the value range of high precision and good stability is τ=6, ε =4 and 0<θ<0.6.